2017
DOI: 10.4269/ajtmh.16-0436
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasite Infections and Accuracy of Direct Thin and Thick Smear, Formol-Ether Sedimentation, Centrifugal Flotation, and Mini-FLOTAC Techniques Among Patients with Gastrointestinal Tract Disorders from the Greater Cairo Region, Egypt

Abstract: Abstract. The aim of the present study was to assess the frequency of intestinal parasitic infection among patients with gastrointestinal tract disorders from the Greater Cairo region, Egypt. In addition, a comparison was made of the accuracy of direct thin and thick smear, formol-ether sedimentation (FEC), centrifugal flotation (CF), and mini-FLOTAC techniques in the diagnosis of infection. Out of 100 patients, the overall prevalence of parasitic infection was 51%. Only 6% had dual infection. Giardia lamblia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In agreement the study done by Barda et al [7] confirmed that the mini-FLOTAC sensitivity for helminthes was 95% and FECM sensitivity for protozoa was 88%. Also, our results are close to the study done by Hussein et al [3] in which mini-FLOTAC sensitivity for helminthes was 100% and FECM sensitivity for protozoa was100%. An important observation is that the diagnostic accuracy of the mini-FLOTAC changes according to the FS used.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement the study done by Barda et al [7] confirmed that the mini-FLOTAC sensitivity for helminthes was 95% and FECM sensitivity for protozoa was 88%. Also, our results are close to the study done by Hussein et al [3] in which mini-FLOTAC sensitivity for helminthes was 100% and FECM sensitivity for protozoa was100%. An important observation is that the diagnostic accuracy of the mini-FLOTAC changes according to the FS used.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with several studies [20,22,30] which detected higher sensitivity of FS2 in helminthes detection. Hussein et al [3] revealed that FS7 was generally more sensitive (100%) for helminthes diagnosis but with no significant difference between FS2 and FS7. This disagreed completely with the findings of our study in which FS7 was less sensitive (58.3%) in helminthes diagnosis with a significant difference between FS2 and FS7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that all helminthes found were Enterobius vermicularis nematodes. Could be due to the methods of diagnosis used in this study, this variation is not significant at all and may reflected that direct smear methods are less sensitive and required triplicate successive examination which is not applied here and that referred previously by others [32]. .…”
Section: The Rate Of Infection Of the Parasites That Causes Gp In Examentioning
confidence: 64%
“…In studies to assess the frequency of intestinal parasitic infection in Egypt, Giardia lamblia was recorded in 34.3% of stool samples by IFAT in a report from Menoufia governorate [1] ; and 37% of water samples from different districts in Alexandria city also by flow cytometry [2] . A more recent report from greater Cairo recorded 26% infectivity [3] .…”
Section: Introductionmentioning
confidence: 94%